Anion size control of the packing in the metallic versus semiconducting chiral radical cation salts (DM-EDT-TTF)2XF6 (X = P, As, Sb). Issue 84 (3rd October 2016) - Pop, Flavia; Auban-Senzier, Pascale; Canadell, Enric; Avarvari, Narcis
Abstract : Tuning of the structural type and conducting properties have been achieved through chirality of the precursor and anion size. Abstract : Control of the structural type in metallic enantiopure and racemic radical cation salts is achieved through hydrogen bonding interactions between the chiral donor DM-EDT-TTF and the XF6 anions (X = P, As, Sb), determined by the anion size and the chiral information.